GLOBALIZATION AND ITS IMPACT ON UKRAINE'S ECONOMIC SECURITY: CHALLENGES AND THREATS TO UKRAINE'S ECONOMIC SECURITY - Rykov, Vadym Volodymyrovych (Global Prosperity, 2023)
Analyzing the impact of globalization on the economic security of Ukraine, this article examines the challenges and threats arising in the context of modern global trends. The article assesses how globalization affects the economic aspects and stability of Ukraine, taking into account its potential and vulnerability in the international economic environment. The study describes the relationship between globalization processes and the situation in the Ukrainian economy, and also considers possible strategies and measures to ensure economic stability and protection from the negative effects of global changes. The article examines the consequences and possible threats arising in connection with global processes for the economic stability of Ukraine. The article analyzes the impact of globalization on the key areas of the country's economy and determines the factors that affect the economic security of Ukraine in the conditions of growing integration in the world market. The study of the article also offers possible strategies and recommendations for strengthening the economic security of Ukraine in the conditions of globalization The state policy of guaranteeing the economic security of Ukraine in the conditions of globalization processes has been improved, namely: the implementation of mechanisms of adaptive and sustainable development and the development of a structured model of an adaptive system for ensuring the stability of the national economic system and its economic security, which is based on the methodological principles of multiplicity, integrity, reliability, synergy, hierarchy, emergency, adaptability, purposefulness; formation and development of subsystems of regulation and planning and the corresponding management mechanism (external and internal influence) in terms of phases of design reflection and implementation.